Contaminants in Honey: Safeguarding Quality and Consumer Health - Kaur, Khushmeen; Arora, Pratham; Gupta, Garima (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2024)
Honey, produced largely by European Honey Bees, Apis mellifera. It possesses qualities that can be used to cure cancer, wounds, and ailments. The presence of environmental pollutants in honey, poses a significant risk to its therapeutic benefits and the safety of consumers. Antibiotics such as amphenicols, tetracyclines, beta lactams, and others, commonly used to treat multiple diseases in bees, are been found in honey. The presence of antibiotic residue in honey can cause many health issues in humans, such as anemia, enamel hypoplasia, and nephrotoxicity. Residues of pesticides derived from flowers and pollen of treated crops have the potential to induce skin infections, cancer, neurological impairment, and bruising. Pesticides have the ability to harm cells and influence human genetics. Clostridium botulinum spores, known to cause botulism in infants, have been discovered in honey. Zinc, mercury (Hg), copper (Cu), and other heavy metals are toxic and have carcinogenic properties. They can lead to the development of cancer, anemia, heart failure, lung failure, renal failure, and gastrointestinal failure. Heavy metals possess carcinogenic and deleterious properties. This study focuses on the importance of exercising caution while using adulterated honey. Additionally, it highlights the significance of implementing stringent global regulations to ensure honey bee safety and maintain the purity of honey.